5.4k views
4 votes
Drag values to complete each equation.

Drag values to complete each equation.-example-1
User TommySM
by
5.9k points

2 Answers

3 votes

Answer:


9^(-7) and
9^(-2)

Explanation:

using the rules of exponents


(a^m)^(n) =
a^(mn)


a^(m) ×
a^(n) =
a^((m+n))


(a^(m) )/(a^(n) ) =
a^((m-n))

given (
9^(5) ×
9^(-9) ) /
9^(3)

=
(9^(5+(-9)) )/(9^(3) ) =
(9^(-4) )/(9^(3) ) =
9^(-4-3) =
9^(-7)

given
(9^4)^(3) ×
9^(-14)

=
9^(12) ×
9^(-14)

=
9^(12+(-14)) =
9^(-2)


User Gentle
by
5.7k points
3 votes

Answer: The required values of the given expressions are


(9^5.9^(-9))/(9^3)=9^(-7),~~~(9^4)^3.9^(-14)=9^(-2).

Step-by-step explanation: We are given to find the values of the following expressions :


E_1=(9^5.9^(-9))/(9^3)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\\\E_2=(9^4)^3.9^(-14)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)

We will be using the following properties of exponents :


(i)~x^a.x^b=x^(a+b),\\\\(ii)~(x^a)/(x^b)=x^(a-b)\\\\(iii)~(x^a)^b=x^(ab).

From expression (i), we get


E_1\\\\\\=(9^5.9^(-9))/(9^3)\\\\\\=(9^(5+(-9)))/(9^3)\\\\\\=(9^(-4))/(9^3)\\\\\\=9^(-4-3)\\\\=9^(-7)

and from expression (ii), we get


(9^4)^3.9^(-14)\\\\=9^(4*3).9^(-14)\\\\=9^(12).9^(-14)\\\\=9^(12+(-14))\\\\=9^(-2).

Thus, the required values of the given expressions are


(9^5.9^(-9))/(9^3)=9^(-7),~~~(9^4)^3.9^(-14)=9^(-2).

User Karsten
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.